1991
DOI: 10.7326/0003-4819-115-4-266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triple Therapy (Antibiotics plus Bismuth) on Duodenal Ulcer Healing

Abstract: Combined therapy with anti-H. pylori agents and ranitidine was superior to ranitidine alone for duodenal ulcer healing. Our results indicate that H. pylori plays a role in duodenal ulcer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(71 citation statements)
references
References 14 publications
5
64
0
2
Order By: Relevance
“…Helicobacter pylori is a causative agent for duodenal and peptic ulcers (17,49), and infection with H. pylori is a risk factor for gastric adenocarcinoma (14) and for B-cell MALT lymphoma (37). H. pylori infection in Western countries occurs in up to 50% of the population (16) and may reach 90 to 100% in developing countries (15), where antibiotic resistance rates are also high (15).…”
mentioning
confidence: 99%
“…Helicobacter pylori is a causative agent for duodenal and peptic ulcers (17,49), and infection with H. pylori is a risk factor for gastric adenocarcinoma (14) and for B-cell MALT lymphoma (37). H. pylori infection in Western countries occurs in up to 50% of the population (16) and may reach 90 to 100% in developing countries (15), where antibiotic resistance rates are also high (15).…”
mentioning
confidence: 99%
“…Subsequently, an RCT of both colloidal bismuth subcitrate and cimetidine, alone or in combination with tinidazole, confirmed that colloidal bismuth subcitrate and tinidazole cleared the infection in almost 75% of patients [7] . With the addition of a second antibiotic, tetracycline or amoxicillin, eradication rates in later RCTs exceeded 80% [8][9][10] . However, there were some problems associated with bismuth-based triple therapy, which included the number of tablets patients were required to take, the duration of therapy, and side effects such as altered taste, nausea, and diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori infection elicits gastric inflammation and may cause gastritis, peptic ulcers, duodenal ulcers, and gastric adenocarcinoma (5,10,20,59). The motility of H. pylori is an essential requirement for colonization of the gastric niche (13,14).…”
mentioning
confidence: 99%